2003
DOI: 10.1590/s0100-879x2003001000016
|View full text |Cite
|
Sign up to set email alerts
|

Use of erythromycin for the treatment of severe chronic constipation in children

Abstract: The efficacy of erythromycin was assessed in the treatment of 14 children aged 4 to 13 years with refractory chronic constipation, and presenting megarectum and fecal impaction. A double-blind, placebocontrolled, crossover study was conducted at the Pediatric Gastroenterology Outpatient Clinic of the University Hospital. The patients were randomized to receive placebo for 4 weeks followed by erythromycin estolate, 20 mg kg -1 day -1 , divided into four oral doses for another 4 weeks, or vice versa. Patient out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Table 3 presents the characteristics of the 28 included studies; there were 21 RCTs, 1 CCT26 and 6 crossover studies 15 17 25 30 37 42…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 presents the characteristics of the 28 included studies; there were 21 RCTs, 1 CCT26 and 6 crossover studies 15 17 25 30 37 42…”
Section: Resultsmentioning
confidence: 99%
“…Of the crossover studies four were hospital based, of which two were conducted at a general paediatric department15 30 and two were conducted in a paediatric gastroenterology department 17 25. Only one study was primary care based 37…”
Section: Resultsmentioning
confidence: 99%
“…1 study of 14 children showed some significant results: Further evaluation through RCTs is needed to assess erythromycin as an adjunct in chronic constipation [73]. …”
Section: Evidence Base For Medications Used In Treatment Of Constipatmentioning
confidence: 99%
“…Besides constipation-related IBS, several studies have also suggested abnormalities of colonic bacterial composition in chronic idiopathic constipation [125]. Here again antibiotic treatment with vancomycin [126,127], rovamycin (in combination with diphetarsone, an amebicidal agent) [128,129] or erythromycin [130], which, however, displays a prokinetic activity [131,132], proved to be capable of reversing long-lasting constipation. Furthermore, the efficacy in both clinical conditions of probiotics [133][134][135] lends further support to the pathogenic role of bowel flora.…”
Section: Ibs and Chronic Constipationmentioning
confidence: 99%